PROFILE OF SECONDARY SCHOOL STUDENTS WITH HIGH MATHEMATICS ABILITY IN SOLVING SHAPE AND SPACE PROBLEM - Putra, Mulia; Novita, Rita (Journal on Mathematics Education, 2015)
This study aimed to describe the profile of secondary school students with high mathematics ability in solving shape and space problem in PISA (Program for International Student Assessment). It is a descriptive research with a qualitative approach, in which the subjects in this study were students of class VIII SMP N 1 Banda Aceh. The results show that in solving the problem PISA on shape and space, high mathematics ability students were able to identify the problem by making the information known from PISA issues related to the shape and space content.Keyword: Profile, Problem Solving, Task of PISA DOI: dx.doi.org/10.22342/jme.61.20